Análisis de metodologías de ataque tipo Clickjacking y Touchjacking, en entorno web. - Valero Sánchez, Irene Mercedes (2023)
The present degree work is the analysis of clickjacking and touchjacking attack methodologies in a controlled environment, the main objective being to determine the level of efficiency of each of these attacks that could be subjected to certain conditions that could be raised in the different scenarios, in the same way the possible mitigation measures suggested by authors are implemented within the analysis carried out, for the development of this case study the following steps were carried out: 1) Analysis of a possible attack scenario 2) Evaluation of possible threats of the attack scenario 3) Development of matrices of possible attacks 4) Determine possible critical vectors of the proposed scenario 5) Evaluation of possible attack and mitigation techniques. For the development of this case study, an experimental method was used in order to modify each of the variables of the proposed scenarios and determine the effects that it causes in each of them, a qualitative method is also implemented in order to determine characteristics and conditions that may present a greater risk against this type of attack. The result of the analysis of clickjacking and touchjacking techniques in this case study seeks to establish possible sanitation measures and implementation of good practices, as well as the use of standards in web development to improve security within web applications.